Advanced Ni tar reforming catalysts resistant to syngas impurities: current knowledge, research gaps and future prospects - Dara Khairunnisa Mohamed (2022)
Catalytic reforming is a promising technology for the removal of tar from syngas. However, due to the presence of other impurities such as H2S, HCl, HBr, siloxanes, alkali metals, and NH3, the lifetime, activity, and stability of commonly used Ni-based catalysts is limited. This review investigates the recent findings related to poisoning effects of both common and under-researched syngas impurities on nickel catalysts and achievements in the synthesis of poison tolerant catalysts. The source and content of impurities produced from the gasification of different feedstock are examined. As current catalysts used for tar reforming require further improvement to ensure tolerance to poisoning, two approaches for catalytic tar reforming gas products from gasification of biomass/solid waste with and without prior syngas pre-treatment are evaluated to emphasize the importance of developing poison-tolerant catalysts. The deactivation mechanisms of Ni catalysts by syngas impurities, regeneration techniques, and strategies for developing poison-tolerant catalysts are reviewed. Finally, limitations of current catalytic tar reforming processes and promising approaches for future works are further discussed.